Specification for control functions for ISO 7-bit and 8-bit coded character sets (BSI, 1989)
Code extensions, ISO seven-bit coded character set, Coded character sets, Code extension characters, Control characters, Graphic characters, Coded representation, Computer terminals, Computer typesetting